Rehabilitation in acute post COVID-19 symptoms with intracranial space occupying lesion: a case report - Rafii, Qory Fitrahtul Aqidah; Hidayat, M. Fitrah; Aryudha, Teja (International Journal of Research in Medical Sciences, 2021)
Coronavirus disease (COVID-19) is an infectious disease caused by the SARS-CoV-2. Older people and those with underlying medical conditions like cardiovascular disease, diabetes, chronic respiratory disease or cancer is more likely to develop serious illness. Acute post COVID-19 patients will get a variety of problems with normal functioning. Rehabilitation could be an effective method for decreasing COVID-19’s effects on patient health and function. A 20 years old, female was diagnosed with COVID-19 5 weeks ago, it had been reported shortness of breath, difficult clearing phlegm, headache, nausea and vomiting. The patient had a history of intracranial space occupying lesion (SOL), cerebello pontine angle (CPA) tumor 3 years ago, craniotomy resection of 4th ventricular tumour one year ago and a second craniotomy scheduled for 2021. Several exercises were scheduled for patients including prone position, respiratory muscle training, controlled breathing techniques, bronchial hygiene-airway clearance techniques, aerobic exercise, three times a week, exercises were scheduled. After having completed the exercise program for four weeks, exercise improved shortness of breath, phlegm expenditure, muscle strength, improve lung recoil, vital capacity, range of motion, patient balance and the patient’s ability to maximize activity.